Analysis of thermostat control in dutch dwellings: occupants’ behavioral profiles - Bedir, Merve (A+BE | Architecture and the Built Environment, 2018)
In the previous Chapter we made a sensitivity analysis based on actual energy consumption and heating behavior, on the whole OTB sample using methods like Markov chain and Monte Carlo analysis. In this Chapter (Chapter 5) a deeper analysis of heating behavioral patterns is reported. The study included 61 houses randomly chosen from the Netherlands, monitored for 2 months during March and April 2011. The thermostat use patterns of households were studied as well as chosen maximum and minimum set points each day for the whole sample. Then these patterns were correlated with the household and dwelling characteristics of the sample. Unfortunately, the collected energy consumption data for this sample was not reliable to be included in the analysis. This Chapter deals with the Research Question III-1 of this thesis: (Chapter 1, Section 3, pg. 16-17) “ III. What are the behavioral patterns and profiles of energy consumption? The sub-question is: What are the behavioral patterns of thermostat control? How do they relate to the household characteristics, revealing behavioral profiles?” The research reported in this Chapter was conducted by Bedir, borrowing the dataset of Sonja van Dam. The data was collected through monitoring, by and for Sonja van Dam for her PhD research, using ENECO’s means of data collection. The analysis in this Chapter was done, and the paper was written by Bedir. The co-author has given permission to include this research in this thesis. This chapter is being prepared to be published as a scientific journal article. It was formerly published as a conference paper: Bedir, M. Van Dam, S. (2013) Analysis of Thermostat Control Behavior in Dwellings: Evidence from monitoring in the Netherlands. Plea 2013, Proceedings of 29th Conference of Sustainable Architecture for a Renewable Future, Germany (CD)